Allergic ebook A graphic novel. - Lloyd, Megan Wagner (2021)
A coming-of-age middle-grade graphic novel featuring a girl with severe allergies who just wants to find the perfect pet! At home, Maggie is the odd one out. Her parents are preoccupied with getting ready for a new baby, and her younger brothers are twins and always in their own world. Maggie loves animals and thinks a new puppy to call her own is the answer, but when she goes to select one on her birthday, she breaks out in hives and rashes. She's severely allergic to anything with fur! Can Maggie outsmart her allergies and find the perfect pet? With illustrations by Michelle Mee Nutter, Megan Wagner Lloyd uses inspiration from her own experiences with allergies to tell a heartfelt story of family, friendship, and finding a place to belong.